Newell and Shanks' approach to psychology is a dead end. Issue 1 (24th January 2014) - Dijksterhuis, Ap; van Knippenberg, Ad; Holland, Rob W.; Veling, Harm
Abstract: Newell & Shanks (N&S) criticize theories on decision making that include unconscious processes. To the extent that their own perspective becomes apparent, however, it is dated, implausible, and at odds with the major developments of the past decades. Their conclusions are, at least for research areas we feel entitled to evaluate, based on a biased sampling of the literature.